Delhi’s Dialects in the Collection Sketches of Ashraf Sabohi - Shah, Rabia; Yousafzai, Altaf; Hassan, Nadeem (Makhz (Research Journal), 2025)
Delhi ki chand ajeeb hastehan are a combination of Ashraf Sabui’s sketches. This book contains fifteen sketches. The roles of these sketches are representative of the culture of Delhi. Through these sketches, Ashraf sabohi is a linguistic civilization of Delhi. Ashraf Sabohi has new climate in his particular Delhavi style to write sketches Of the civilized symbols of this historic city.The axis of Ashraf Sabohi,s sketches is the Common man of Delhi who talks in Urdu. Through these sketches, Ashraf sabohi has also shown a glimpse of these dialects. Their sketches are familiar with the bids of the fort.In these sketches, different people are speaking in different bids of delhi. He has new Climate in his particular Dahlavi style in writing the sketches of the civilized symbols of this historic.The Urdu language ,which was a special language in ancient Delhi, has played with the language of his characters. The people of these sketches appear to be speaking to the Red Fort Code Language Farfari zargari. This sketch of Ashraf Sabohi is a great source of understanding of the ancient dialects of Delhi’s civilization and culture.